Characterisation of kefir-derived lactic acid bacteria and their extracellular vesicles - Puyu Li; Ying Bai; Shiwei Li; Zhiying Zhang (Current Research in Food Science)
The signalling effects of microbial biofilms and extracellular polysaccharides (EPS) determine the stability of microbial communities. As messenger molecules, extracellular vesicles (EVs) mediate the interactions of microbial populations by carrying cargo. Therefore, this study took biofilm and EPS as screening factors, preliminarily explored the basic characteristics of strains with strong biofilm formation ability and high EPS production. The results showed that the EVs concentration of three lactic acid bacteria (KLK29, KLH2 and KEF14) were high. The concentration of their EVs was proportional to the EPS production, indicating that EVs were directly involved in the formation and regulation of EPS, but it did not mean that EVs could directly affect other biological characteristics of the strains. This study offers crucial information about kefir-derived strains and their EVs, and provides a preliminary research basis for EVs-mediated expression of probiotic characteristics of strains in kefir.